PENGARUH EKSPEKTASI USAHA TERHADAP HEDONIC MOTIVATION, HABIT DAN NIAT PERILAKU PENGGUNAAN APLIKASI TRANSPORTASI ONLINE (Studi Pada Pelanggan Gojek Indonesia Di Kota Malang) - Yuliana, Ana; Astuti, Endang Siti; Afrianty, Tri Wulida (FIA UB, 2020)
The development of the internet which is integrated with the smartphone application technology has made the business of transportation serviceÂ innovate by adopting online transportation applications. Online transportation applications are important to know whether the technology is really accepted by users. This paper provides literature Â for use as a reference in research into the acceptance and use of information technology with the UTAUT2 model. GOJEK is an online transportation application that provides solutions and convenience in daily activities. In fact, the desire to use the GOJEK application is not only because of the need for convenience, but also because of the urge to get pleasure and habits using the GOJEK application in daily activities. In proving the statement, this research builds a conceptual model and hypothesis formulation that is used to conduct research on the use of online transportation applications. This study will useÂ sample of 130 customers who have used the GOJEK application for 1 or 3 months, then the data will be processed using PLS.